Did Covid-19 Pandemic Influence The Capital Structure of Healthcare Firms? - Widodo, Fran Sagita; Achsani, Noer Azam; Bandono, Bayu (School of Business, IPB University (SB-IPB), 2024)
Background: The Covid-19 pandemic will have an impact on the funding strategies of companies in the health sector, as fluctuations in income will play a significant role in determining their ability to finance various activities. This phenomenon will manifest itself in the context of capital structure policy determinations.Purpose: This study aimed to investigate the impact of COVID-19 on the capital structure behavior of healthcare companies in Indonesia. Design/methodology/approach: Utilizing the data from fourteen companies that were listed on the Indonesia Stock Exchange for the period of 2017–2022, a panel data regression based on the Generalized Least Squares (GLS) approach was used to analyze the impact of COVID-19 and other factors on the capital structure decision. Furthermore, the partial adjustment model with the Generalized Method of Moments (GMM) estimator was employed to measure the speed of adjustment toward target leverage. Findings/Result: We found COVID-19 had a significant impact on capital structure. Other factors that influenced the capital structure were the return on equity, current ratio, and growth. Finally, the healthcare companies in Indonesia readjusted their capital structure toward target leverage at a rapid rate. Managers of companies in the health sector can arrange considerations according to the order of funding sources, using internal funding sources first in the form of retained earnings, then debt, and if necessary, issuing equity.Conclusion: During a crisis, the effects experienced by different sectors exhibit variations. Consequently, conducting sector analysis research during a crisis becomes crucial in order to ascertain the precise impact of specific crises on particular sectors.Originality/value (State of the art): This research contributes to the existing literature on capital structure decision and speed of adjustment by adding the COVID-19 crisis dimension, especially when the industry play the important rule. Keywords: capital structure, COVID-19, GLS, GMM, speed of adjustment